SEBUAH ALGORITMA POHON KEPUTUSAN UNTUK KLASIFIKASI CITRA SATELIT AQUA MODIS - Rina Luciane Manuhutu; Riana Debora Hutagalung (Universitas Ahmad Dahlan, 2010)
The satellite image processing for the environmental eksploration requires data accuracy which implied in every pixel of image so that required an appropriate technique of classification. The suitable classification is decition tree classification technique. Research about decition tree classification for classification data of satellite image have done and also research about Aqua MODIS satellite image processing for environmental exploration, but the decition tree classification technique is not developed yet for the classification of Aqua MODIS satellite data image. In this research, an algorithm decition tree classification method for data processing of Aqua MODIS satellite image to determine sea surface temperature classification is developed. A case study conducted at territorial Moluccas waters. The result of this research show that mean of accuration data classification of sea surface temperature is 97.6%